2018
DOI: 10.3390/jcm7120466
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Functional Near-Infrared Spectroscopy (fNIRS) Neuroimaging in Exercise–Cognition Science: A Systematic, Methodology-Focused Review

Abstract: For cognitive processes to function well, it is essential that the brain is optimally supplied with oxygen and blood. In recent years, evidence has emerged suggesting that cerebral oxygenation and hemodynamics can be modified with physical activity. To better understand the relationship between cerebral oxygenation/hemodynamics, physical activity, and cognition, the application of state-of-the art neuroimaging tools is essential. Functional near-infrared spectroscopy (fNIRS) is such a neuroimaging tool especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
307
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 308 publications
(336 citation statements)
references
References 364 publications
6
307
1
4
Order By: Relevance
“…However, independent of the degree of behavioral improvements, almost all reviewed studies reported profound changes in brain activation (especially in the frontal lobe, the cerebellum, and the hippocampus) in response to exercise (see Table 1). In general, the observations of a higher activation in distinct regions of the frontal lobe and cognitive improvements after exercise cessation are in line with the findings provided by other functional neuroimaging techniques (i.e., fNIRS) [34].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…However, independent of the degree of behavioral improvements, almost all reviewed studies reported profound changes in brain activation (especially in the frontal lobe, the cerebellum, and the hippocampus) in response to exercise (see Table 1). In general, the observations of a higher activation in distinct regions of the frontal lobe and cognitive improvements after exercise cessation are in line with the findings provided by other functional neuroimaging techniques (i.e., fNIRS) [34].…”
Section: Resultssupporting
confidence: 88%
“…In this regard, the use of neuroimaging methods offers great potential for acquiring a deeper understanding of physical exercise-induced changes in the neural correlates of cognition, such as changes in functional brain activation [33][34][35]. The most common methods used to investigate effects on functional brain activation are functional near-infrared spectroscopy (fNIRS) [34] and electroencephalography (EEG) [36,37]; however, also functional magnetic resonance imaging (fMRI) has recently been applied in the context of acute physical exercise and cognition [38,39]. The strengths of fNIRS and EEG compared to fMRI are a higher temporal resolution, greater portability, and applicability in almost all cohorts (e.g., for individuals with metallic implants or claustrophobia) [34,40,41].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty to 30 min of moderate intensity (50-60% VO 2max ) cycling increased post-exercise cortical oxygenation (i.e., activation), which aligned with improvements in post-exercise executive function performance (Stroop task) (Yanagisawa et al, 2010;Stavres et al, 2017;Tsubaki et al, 2018). Increased PFC oxygenation may be indicative of higher cortical activity and, therefore, greater mental effort leading to improved cognitive processes such as working memory and attention (Herold et al, 2018). However, a negative association between left-PFC activation and processing speed has been recently reported among middle aged adults after acute bouts of both low and high intensity aerobic exercise, along with yoga (Moriarty et al, 2019).…”
Section: Brain Blood Flow and Oxygenationmentioning
confidence: 82%
“…Additionally, the focus is increasingly shifting in the direction of investigating neural correlates of motor expertise comparing athletes and non-athletes using fNIRS (Seidel et al, 2017(Seidel et al, , 2019. In combination with novel approaches such as multichannel whole-brain fNIRS, multi-distance fNIRS Seidel et al, 2019) and systemic physiological augmented fNIRS (Herold et al, 2018), these studies provide an important basis for neurodiagnostics of motor expertise and talent (see Figure 1B). Furthermore, a combination of non-invasive brain imaging techniques might help to overcome limitations in spatial and/or temporal resolution.…”
Section: Diagnostics Of Neuroplasticity Using Non-invasive Brain Imagmentioning
confidence: 99%